RESEPSI MASYARAKAT KABUPATEN LEBAK PROVINSI BANTEN TERHADAP UPACARA SEBA SUKU BADUY - Octavitri, Yollanda (Sastra Indonesia, Fakultas Ilmu Budaya, 2012)
ABSTRACTSeba Ceremony tradition is a ceremonial, cultural expression or gratitudeform for the harvest produced for one year and an expression of thanks andrespect from the Baduy Tribe to Regent of Lebak as the leader of the Baduy Tribeliving place. The Seba Ceremony Implementation creates a good relationshipbetween the Baduy Tribe and bureaucrats. Seba Ceremony is held every year, between April-May in the year AD.The tribute given to local regent has a motive from the custom obligation,gratitude, expectancy and prayer. Gratitude, expectancy and prayer are deliveredverbally by an official of the Baduy Tribe and it is realized with the dedication ofharvest. It has a local wisdom of the simplicity of the Baduy Tribe life. The data in this research come from verbal information, from the objectsand informants. Data is collected by several steps that are non-participationobservation, interviews and questionnaires. It produces data about surroundingsconditions of the Baduy Tribe, the story of Seba Ceremony, and also the societyresponse to Seba Ceremony. This research uses theory of folklore, theory of philology and the theory ofliterary reception. Folklore theory is used to describe Seba Ceremony as part ofpartly verbal folklore. Philological theory is used in the process of verbal text data collection that contained in the Baduy Tribe and documenting traditional ritualprocession of Seba Ceremony. Literary reception theory as a basis to determinethe response of the stories, processions of traditions and meaning that contained inthe Seba Ceremony of the Baduy Tribe. By means of these theories, it can beknown that Seba Ceremony tradition provides an overview and outlook on life ofLebak Regency Society.The result of this research showed the reception of Lebak Regency SocietyTo Seba Ceremony in general is respect and appreciation. Specifically, thevariation of Reception of Lebak Regency Society is motivated by several factors:age, educational level and cultural status.